2015
DOI: 10.1007/s10973-015-5073-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic characterization of human carbonic anhydrase VB stability and intrinsic binding of compounds

Abstract: The thermodynamics of low molecular weight synthetic sulfonamide inhibitor binding to carbonic anhydrase (CA) VB was determined by the isothermal titration calorimetry (ITC) and the fluorescent thermal shift assay (FTSA). ITC provided the enthalpic and entropic contributions to the binding affinity of ethoxzolamide to CA VB. FTSA is a high-throughput assay that measures protein thermal stabilization by added ligands. FTSA enabled determination of extremely high affinity of several compounds binding to CA VB. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…The carbon anhydrase (CA) gene family plays an important role in CO 2 emission and acid-base regulation in fish (Gilmour and Perry, 2009;Fehsenfeld and Weihrauch, 2013). CA-VB is widely distributed in the tissues of humans and mice and participates in carbon metabolism and pH homeostasis (Kasiliauskait et al, 2015). Previous studies have also found that CA and CAHZ genes are differentially expressed in populations of L. waleckii living in a highly alkaline environment (Xu et al, 2013b;Chen et al, 2019); these findings concur with our present data.…”
Section: Discussionsupporting
confidence: 92%
“…The carbon anhydrase (CA) gene family plays an important role in CO 2 emission and acid-base regulation in fish (Gilmour and Perry, 2009;Fehsenfeld and Weihrauch, 2013). CA-VB is widely distributed in the tissues of humans and mice and participates in carbon metabolism and pH homeostasis (Kasiliauskait et al, 2015). Previous studies have also found that CA and CAHZ genes are differentially expressed in populations of L. waleckii living in a highly alkaline environment (Xu et al, 2013b;Chen et al, 2019); these findings concur with our present data.…”
Section: Discussionsupporting
confidence: 92%
“…Solid curve is a fit of the model, solid line is intrinsic Gibbs energy of binding, dashed line is a fraction of ligand, dotted line is a fraction of protein. Experiments were performed in universal buffer made of 50 mM sodium phosphate, 50 mM sodium acetate, and 25 mM sodium borate containing 100 mM NaCl and up to 2% DMSO as previously described in: CA I and CA II (Morkūnaitė et al ., 2015), CA IV (Mickevičiūtė et al ., 2017), CA VB (Kasiliauskaitė et al ., 2016), CA VI (Kazokaitė et al ., 2015), CA VII (Pilipuitytė and Matulis, 2015), CA IX (Linkuvienė et al ., 2016 b ), CA XII (Jogaitė et al ., 2013), CA XIII (Baranauskienė and Matulis, 2012), and CA XIV (Juozapaitienė et al ., 2016). All panels are drawn at the same scale to help visualize the differences in affinities of binding.…”
Section: Observed Versus Intrinsic Thermodynamic Binding Parametersmentioning
confidence: 99%
“…To better understand the interaction mechanism and its pH dependency, we have here exploited our previous observation that it is possible to determine the intrinsic binding thermodynamic constants for CA inhibitors by analyzing the pH-dependency of these interactions and, for the first time here, determine the intrinsic rate constants by using surface plasmon resonance (SPR) biosensor technology. Although SPR-based kinetic analysis of interactions between drug-like compounds and target proteins has become a key method for drug discovery, and has been a subject of several reviews, it is yet not used to its full potential for characterizing the details of molecular interactions.…”
Section: Introductionmentioning
confidence: 99%